Does the stability of farmland rental contract & conservation tillage adoption improve family welfare? Empirical insights from Zhangye, China. (August 2021) - Si, Ruishi; Lu, Qian; Aziz, Noshaba
Abstract: China's farmland rental markets have brought new strategies to improve farmland quality by adopting conservation tillage (CT) and improving family welfare. In the existing literature, little attention is given to this phenomenon. Hence, the current research is attempted to explore the family welfare outcome of transferees adopting CT compared with traditional tillage (TT). Data from 652 households have been collected from Zhangye, China, to meet the study objective by employing the endogenous switching regression model (ESR). The results showed that farmland rental contract positively and significantly influences transferees' decision to adopt CT and improve family welfare. The findings further endorsed inverted U-shaped relationships with the optimal turning point of 6.5 and 8 years of the contract period. More importantly, considering the sample selection and endogenous issues of the transferee's decision to adopt CT, the findings further showed that if the transferee adopting CT switch to adopt TT, the welfare level of the family will be decline by 0.1985. And if the transferee adopting TT switch to adopt CT, then it is likely that the welfare level of the family will be rise by 0.1785. The empirical findings of the current study provide guidelines for policy makers to stabilize farmland rental contracts and encourage farmers to opt CT application for the family's overall welfare. Highlights: Rural labor force migration has provided an advantageous condition for activating the farmland rental market. Farmland rental markets have set new avenues to improve farmland quality. Farmland rental contract exerts a positive and significant influence on transferees' decision in adopting CT and overall family welfare. The effects of farmland rental contract on CT adoption and family welfare present an inverted U-shaped relationship.